Pendidikan Karakter Melalui Program Ikatan Pelajar Muhammadiyah di SMP Muhammadiyah 62 Kanupaten Tapanuli Tengah - Tanjung, Rahman Rizki (Universitas Labuhanbatu, 2023)
Character education is one part of the education system that is very important in shaping a person's personality. In the era of increasingly advanced globalization, character education is becoming increasingly important to form a generation with charity. Through the active Muhammadiyah Student Association program designed by branch leaders together with coaches and teaching staff, students can provide moral development for the better. This study aims to find out the concept of character education through the Muhammadiyah student association program, know the character education process through the Muhammadiyah student association program, and also find out the supporting and inhibiting factors of the character education process through the Muhammadiyah student association program at SMP Muhammadiyah 62 Central Tapanuli Regency. The research method carried out is qualitative, research aimed at describing and analyzing the phenomenon of social activity events, attitudes, beliefs, perceptions, thoughts of people individually and in groups. Data analysis techniques are carried out by fulfilling four stages, namely data collection, data reduction, data display and conclusions. From the research that has been done, it can be concluded that the concept of character education through the Muhammadiyah student association program is carried out in accordance with the educational curriculum and activity schedule of the program without disturbing the teaching and learning process that takes place, and the school, so that in implementing the school program and also the Muhammadiyah student association are mutually sustainable and also mutually beneficial, the character education process through the Muhammadiyah student association program is by always carrying out programs that have been prepared by the general leadership and also accompanied by IPM coaches. The programs are mabit, ishoma, morning apple and also muhadarah, these programs are always routinely implemented so that changes can be seen to cadres, especially students as expected, supporting and inhibiting factors of the character education process through the Muhammadiyah Student Association program, namely: There are several kinds of supporting factors, for example, the school environment, motivation and support from parents and support from the community. The inhibiting factor is that parents need the helpof their children and also some cadres are not healthy.